Urban Planning and Resilience Building in the Caribbean : 360° Resilience Background Paper - Johnson, Cassidy (World Bank, Washington, DC, 2021)
Urban Planning is often touted as one of the key actions for achieving sustainable and resilient development, and it is seen as a key element for reducing disaster risks in urban areas. It is especially important for managing urban growth and increasing resilience in already built-up urban areas. However, urban planning is a complex process that depends on a number of integrated foundational elements for its functioning, including for example, politics, cadastral management, building control, a host of regulatory and legal mechanisms, financing and environmental management. Additionally, in order to reduce risks to natural and humanmade hazards, good information about potential hazards and existing vulnerabilities are needed. Most low- and middle-income countries struggle to have sufficient foundational systems in place to enable urban planning to address disaster risks, and this is also true across much of the Caribbean region. Yet, in the context of urban growth, land-scarcity, fragile ecosystems, increasing climate-related hazards and informal development, the Caribbean region requires increased attention across the foundational aspects that enable planning. This research addresses the complex and integrated nature of urban planning and looks at the different foundational aspects that urban planning requires to enable it to guide resilient development and reduce disaster risks. It proposes and employs a methodology for examining eight “Building Blocks” of urban planning and applies this to urban planning practices in nine Caribbean countries, to assesses how much disaster risk management is being integrated into planning across the Caribbean. The nine Caribbean countries are: Belize, Dominica, Dominican Republic, Guyana, Haiti, Jamaica, St Lucia, St Maarten, and St Vincent.